Kinesiotaping, does it really prevent sports injuries? - Kaplan, Y. (British Journal of Sports Medicine, 2021)
Background Over the last 50 years kinesiotaping has become a very popular adjunct in the treatment of sports injuries. Its role in sports injury prevention however remains unclear.